Strategic Human Resource Planning and Workforce Demographics: A Quantitative Analysis - Pokharel, Yadav Prasad; Kirti; Mahat, Dipak (Academia Journal of Research and Innovation, 2026)
This study examines workforce demographic factors with respect to Strategic Human Resource Planning (SHRP) in an organization․ It took a quantitative survey approach and collected data from 150 respondents across various levels of hierarchy in the organization․ Respondents were mostly male (87․3%)‚ with those aged 36 to 45 years being in the majority (32․0%)․ The data were analyzed descriptively and inferentially‚ with a view to ascertaining whether SHRP perceptions were statistically considerably affected by gender‚ age‚ qualification‚ and position․ The findings showed high mean SHRP scores (mean = 4․70 on a scale of one to five)‚ showing an overall agreement with the concept of calculated HR․ Kendall’s tau-b correlation indicated no meaningful correlation (τ = ․019‚ p = ․766) between SHRP and work experience when controlling for other factors․ Independent samples t-tests and one-way ANOVA results showed no important differences in SHRP scores across gender (t = 1․328‚ p = ․186)‚ age groups (F = 1․063‚ p = ․377)‚ education (F = 1․681‚ p = ․157)‚ or job position (F = 0․745‚ p = ․527)‚ indicating consistent‚ positive SHRP perceptions across the workforce and general organizational commitment